A fluorescent probe strategy for the detection and discrimination of hydrogen peroxide and peroxynitrite in cells - Bolland, HR; Hammond, EM; Sedgwick, AC (Royal Society of Chemistry, 2022)
Aryl boronate fluorescent probes allow the non-invasive study of dynamic cellular processes involving the reactive species, hydrogen peroxide (H2O2) and peroxynitrite (ONOO−). However, the ability of these probes to differentiate between these two species remains unclear. Here, we report a boronate-functionalised hemicyanine dye (HD-BPin) as a potential strategy to distinguish between H2O2 at 704 nm (red channel) and ONOO− at 460 nm (blue channel) in solution and in cells. This work also highlights the choice of fluorophore before boronate functionalization can dictate the observed selectivity between these two species.